Pengaruh Cash Ratio dan Debt to Equity Ratio terhadap Return on Equity pada Perusahaan Sub Sektor Telekomunikasi Kriteria Syariah - Kristianingsih Kristianingsih; Dimas Sumitra Danisworo; Satria Hardi Nugraha (Masoem University, 2022)
Competition in the business world requires every company to develop its business to obtain maximum profit. One of them is by improving the performance of the company's management, especially performance in the financial sector. Return on Equity (ROE) is one of the indicators in showing the level of profitability. Many things can affect the achievement of ROE such as liquidity and solvency. This article attempts to investigate more the effect of the liquidity ratio as proxied by the Current Ratio (CR) and the solvency ratio as proxied by the Debt to Equity Ratio (DER). The difference with previous research is that this research was conducted in the infrastructure and utility sector companies, especially the telecommunications sub-sector in Indonesia. This study uses a quantitative approach with a sample of telecommunications sector companies listed on the Indonesia Stock Exchange. The results showed that i) Cash Ratio did not have a significant effect on Return On Equity; ii) Debt to Equity Ratio has a significant negative effect on Return on Equity; and iii) Cash Ratio and Debt to Equity Ratio simultaneously have a simultaneous effect on Return on Equity.